Influência do nióbio na textura e resistência à corrosão de aços inoxidáveis ferríticos em ambientes aerados e desaerados - Ardila, Miguel Angel Narvaez (2013)
This work aims to study the niobium influence in the crystallographic texture and the corrosion resistance of ferritic stainless steels on aerated and de-aerated environments. For this objective the ferritic stainless steels P409, P410, P430A, P430E (Nb stabilized) were used; and austenitic stainless steel, P304, and carbon steel, A36, were used as comparative materials. These materials had a mechanical characterization (hardness and tension test), and the steels P430A and P430E had a crystallographic characterization too. That crystallographic characterization (by EBSD) was analyzed through to inverse pole figure (IPF) and crystal orientation distribution function (CODF). The samples were submitted to anodic potentiodynamic polarization test in solutions: 3.56% NaCl, and 1N H2SO4 on aerated environment, and 3.56% NaCl at de-aerated environment. The samples were examined by SEM after the polarization tests. The analysis of the results clearly showed that the crystallographic texture influence the corrosion resistance. The niobium in the stainless steel reduces the presence of preferential orientation, therefore, the influence of the texture in the corrosion resistance, but helps to increase the corrosion resistance by the formation of niobium carbbonites. Finally it was observed that for polarization tests in aerated environments and de-aerated have a very small variation in behavior that depends on the steel, but this variation is not statistically significant.